Strategi Pengelolaan Sampah Melalui Collaborative Governance Di TPSt Desa Bambe Kabupaten Gresik - Gerry Wahyu Berlia; Anggraeny Puspaningtyas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Being a village with an extraordinary amount of waste production makes the Bambe village government collaborate with several parties in carrying out TPSt development and waste management. This study aims to find out how the process of cooperation that occurs between the Bambe Village Government, the community, and academics that occurs at the Bambe Village TPSt in waste management. The research method used in this study is qualitative. Data collection using literature review, and observation. Based on the findings found by researchers, the cooperation process is still not very good because there are still various obstacles in the process.